Personal Knowledge Management (PKM): Are We Really Ready? - McFarlane, Donovan A. (Journal of Knowledge Management Practice, 2011)
This paper examines the new and emerging branch of Knowledge Management (KM) called Personal Knowledge Management (PKM). While KM is regarded as the parent of PKM, some proponents seek earnestly to distinguish PKM from KM in practice and application. In this paper the author asks an important question with regards to the emergence of a personal knowledge management (PKM) philosophy and branch of study based on arguments that KM itself is evolving and thus, still in a developmental and systematization process, especially as asserted by writers such as McFarlane and Onions, as opposed to the assertions and treatment of KM as a mature branch of management science by Jones, Corner, and Hamalainen, among others. The author explores the philosophical bases of PKM, mainly from the body of knowledge and ideas in Personal Knowledge Management: Individual, Organizational and Social Perspectives and KM theories. The author identifies similar developmental gaps and makes recommendations for PKM practice and progress.
Keywords: knowledge management; Personal knowledge management (PKM); Knowledge management (KM); Knowledge management body of knowledge (KMBOK)